Work-life balance, social connectedness and mental health among working adults in Malaysia - Ling, Esther; Ngoo, Ee Ling; Tan, Sin Yuan (2021)
Although many studies have shown the importance of work-life balance and social connectedness in relation to mental health, poor work-life balance is still one of the major issues imSacWing Woda\¶V ZoUking SoSXlation in Malaysia. There had been no research carried out on social connectedness as the mediator between this association. Correspondingly, this study examines the impacts of work-life balance and social connectedness on mental health problems and on social connectedness as the mediator among working adults in Malaysia. A total of 186 working adults were recruited across Malaysia through an online survey in a cross-sectional design. Multiple linear regression analysis showed that both work-life balance (ȕ = -.193, t(183) = -2.94, p = .004) and social connectedness (ȕ = -.409, t(183) = -6.22, p < .001) significantly predicted the level of mental health problems among working adults. Social connectedness was found to be the strongest predictor. Process SPSS macro analysis indicated that social connectedness significantly mediated the relationship between work-life balance and level of mental health problems (B = -.199, SE = .103, 95% CI [-.425, -021]). These findings are helpful in increasing the awareness of government and human resource management (HRM) to implement policies which facilitates work-life balance and social life, as well as for mental health practitioners in providing them insight for formulating better treatment plans that encourage social connections.